Phase-retrieval algorithm for the characterization of broadband single attosecond pulses - Zhao, Xi; Wei, Hui; Wu, Yan; Lin, Chii D. (My University, 2017)
Recent progress in high-order harmonic generation with few-cycle mid-infrared wavelength lasers has pushed light pulses into the water-window region and beyond. These pulses have the bandwidth to support single attosecond pulses down to a few tens of attoseconds. However, the present available techniques for attosecond pulse measurement are not applicable to such pulses. Here we report a phase-retrieval method using the standard photoelectron streaking technique where an attosecond pulse is converted into its electron replica through photoionization of atoms in the presence of a time-delayed infrared laser. The iterative algorithm allows accurate reconstruction of the spectral phase of light pulses, from the extreme-ultraviolet (XUV) to soft x-rays, with pulse durations from hundreds down to a few tens of attoseconds. At the same time, the streaking laser fields, including short pulses that span a few octaves, can also be accurately retrieved. Such well-characterized single attosecond pulses in the XUV to the soft-x-ray region are required for time-resolved probing of inner-shell electronic dynamics of matter at their own timescale of a few tens of attoseconds.
Citation: Zhao, X., Wei, H., Wu, Y., & Lin, C. D. (2017). Phase-retrieval algorithm for the characterization of broadband single attosecond pulses. Physical Review A, 95(4), 8. doi:10.1103/PhysRevA.95.043407
Keywords: High-Harmonic-Generation; Ray Source Driven; Water Window; Lasers; Streaking; Amplifier